Evolving spatial conservation prioritization with intraspecific genetic data. (June 2022) - Andrello, Marco; D'Aloia, Cassidy; Dalongeville, Alicia; Escalante, Marco A.; Guerrero, Jimena; Perrier, Charles; Torres-Florez, Juan Pablo; Xuereb, Amanda; Manel, Stéphanie
Abstract : Spatial conservation prioritization (SCP) is a planning framework used to identify new conservation areas on the basis of the spatial distribution of species, ecosystems, and their services to human societies. The ongoing accumulation of intraspecific genetic data on a variety of species offers a way to gain knowledge of intraspecific genetic diversity and to estimate several population characteristics useful in conservation, such as dispersal and population size. Here, we review how intraspecific genetic data have been integrated into SCP and highlight their potential for identifying conservation area networks that represent intraspecific genetic diversity comprehensively and that ensure the long-term persistence of biodiversity in the face of global change. Highlights: Conservation area networks on land and sea need to be expanded to meet the objectives of the post-2020 global biodiversity framework. Spatial conservation prioritization (SCP) is a rigorous framework to identify suitable areas for protection on the basis of scientific data. Integrating intraspecific genetic data in SCP can help identify networks of conservation areas that are more representative of biological diversity and likely better at ensuring its long-term persistence.